Frequency of Non-Adherence to Antiepileptic Drugs in Patients with Epilepsy - Nagina Shaikh, Abu Bakar Shaikh, Aijaz Ali, Mujeeb-Ul Rehman, Muhammad Munwar Ali, Suhail Ahmed Aghani (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Epilepsy is a chronic medical ailment or condition that typically causes unexpected, unprovoked repeated seizures that impair a number of mental and physical abilities. Non adherence to antiepileptic drugs is an emerging issue. Objective: To measure the frequency of non-adherence of AEDs among epilepsy patients presenting to a tertiary care hospital Material and Methods: This study was conducted at Chandka Medical College Hospital Larkana and the duration of this study in which this study was completed was 6 months from 29-9-2020 to 29-3-2021. A total of 183 patients were the participants of this study and all the patients were calculated through the calculator of WHO. The method of non-probability sequential sampling was utilized. Forms for ethical approval and permission were completed. The Morisky 8-Item Medication Adherence Questionnaire was used to assess non-adherence. SPSS was used to analyze the data. The P value of 0.05 was deemed important. Results: 183 patients were the participants of this study. There were 103(56.3%) male and 80(43.7%) female. Mean age of patients was 32.1 years ±5.6SD. Among all the patients 183(100%), 68(37%) had non adherence while 115(63%) did not had non adherence to antiepileptic drugs. A substantial association between non adherence and residential status (p=0.02), duration of diseases (p=0.00), educational status (p=0.00), employment status (p=0.00), marital status (p=0.00) and type of medication dose(p=0.00) was found. Conclusion: Non adherence in epileptic patients, resistance to AED therapy has been identified as a key impediment to obtaining the therapeutic aim of seizure independence. Frequency of non-adherence in epileptic patients was moderately high.